Asas Legalitas dalam Hukum Acara Pidana: Kritikan terhadap Putusan MK tentang Praperadilan - Tristam P. Moeliono; Widati Wulandari (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The problem of this research is: how high is the authority of Constitutional Court to amend the provisions of criminal procedure law (KUHAP) by stating that some articles in KUHAP are not constitutional and expanding the authority of judges in pretrial forum. Since 2015, pretrial judges have authority to investigate and decide whether the determination of a suspect is legitimate. The research method was normative juridical. The result shows that Constitutional Court judges have actually replaced the position of lawmakers (legislator) and violated the principles of nullum iudicium sine lege. In relation to that, if the need is to improve the supervision mechanism for the use of coercion in investigations, lawmakers should amend KUHAP or introduce better supervision mechanism for investigators..